Hubungan Lingkungan Sekolah Dan Motivasi Belajar Dengan Keterampilan Sosial Siswa Sekolah Dasar - Rusmin Husain; Yolanda Yolanda (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
This research aims to determine the relationship between the school environment and learning motivation with the social skills of third-grade students at SD Negeri 5 Tilamuta, Boalemo Regency. The objective is to investigate the relationship between learning motivation and students' social skills at Negeri 5 Elementary School in Tilamuta, Boalemo Regency. The research method used in this study is correlational. A sample of 33 students was selected using purposive sampling from a total student population of 187. The results obtained in this study are as follows: There is a correlation between the school environment and children's social skills at Negeri 5 Tilamuta Elementary School, Boalemo Regency, with a correlation coefficient of 42.9%. There is a relationship between learning motivation and children's social skills at Negeri 5 Tilamuta Elementary School, Boalemo Regency, with a correlation coefficient of 19.17%. There is a combined relationship between the school environment, learning motivation, and children's social skills at Negeri 5 Elementary School in Tilamuta, Boalemo Regency, with a correlation coefficient of 68%.